Exploration of the Vinyl-4-Reductase Effector Domain of the Methanogen Specific Transcription Regulator MsvR in Methanosarcina acetivorans - Mundy-Shelton, Kristen (My University, 2017)
Global warming is one of the most pressing issues that this planet faces. Methane production by methanogenic archaea plays a crucial in not only climate change, but also in the global carbon cycle. Methanogenic archaea are strictly anaerobic microorganisms; however, it’s been shown that they have the ability to overcome brief exposure to oxygen. Understanding the systems that play a role in the ability of these methanogens to recover from transient oxygen exposure could lead to greater insight and development of strains that can be more readily engineered for purposes of renewable energy sources. The methanogen specific vinyl-4-reductase domain-containing regulator (MsvR) is a transcription regulator exclusive to methanogenic archaea. This transcription regulator was first discovered in Methanothermobacter thermautotrophicus (Mth) and was shown to regulate its own expression, as well as regulate the expression of the fpaA-rlp-rub operon which has been implicated in response to oxidative stress. Unlike MthMsvR, MsvR homologue in Methanosarcina acetivorans (MaMsvR) was not found to regulate an fpaA-rlp-rub operon, which raised questions as to what other roles this multiple domain transcription regulator may play in regulating responses to environmental stress. This study attempted to look at the individual domains of MaMsvR utilizing MaMsvR truncations and to isolate the V4R effector domain to gain a better understanding of its role in regulating MaMsvR activity in addition to attempting to elucidate the structure of MaMsvR. The data obtained from this study suggested that the V4R domain of MaMsvR contains its own dimerization interface, however, it does not function independently from the DNA binding domain in order to facilitate transcription regulation.
Keywords: Methanogen, Archaea, Transcription, Regulation